Effects of static stretching on squat performance in Division I female athletes - Heisey, C. F; Derek, K. L. (International Journal of Exercise Science, 2016)
Static stretching was once recognized as a method of preparation for physical activity that would inhibit performance and increase risk of injury. However, a growing body of research suggests that static stretching may not have an inhibitory effect. Regardless, the data have not examined gender differences or the fatigue index (FI) and flexibility effects of static stretching on the back squat over multiple sets. Therefore, the purpose of this study was to examine the relationship between a static-stretch condition (SC) and control condition (CC) on flexibility and the FI of Division I female athletes during 4 sets of the back squat. Eighteen subjects (mean ± SD; age 20 ± 1 yrs; height 164.5 ± 14.6 cm; mass 74.1 ± 26.8 kg; waist circumference 73.2 ± 5.4 cm) participated in 3 testing days over the course of 3 weeks. Each subject`s 1RM back squat was assessed during the first day of testing and verified during the second. On the third testing day, subjects assigned to the SC held 3 lower-body stretches twice for 30 second intervals and those assigned to the CC rested during the corresponding 7 minutes and 50 second time period. The subjects also performed a fatiguing squat protocol consisting of 4 sets of maximum repetitions on the third day of testing. A significant (p=0.04) interaction was noted for flexibility. No significant interaction (p=0.41) was observed between the FI of the CC (41.8 ± 24.1%) or the SC (27.6 ± 45.2%). These results indicate that static stretching does not have a significant effect on multiple sets of the back squat. Therefore, coaches may allow their athletes to engage in static stretching prior to resistance exercise ad libitum.